2007
DOI: 10.1111/j.1346-8138.2007.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia cutis originating in the extravasation site of i.v. gabexate mesilate infusion

Abstract: Leukemia cutis is a localized or disseminated skin infiltration by leukemic cells. A 64-year-old man was diagnosed with acute myeloid leukemia (AML) complicated by disseminated intravascular coagulation. During the course of treatment with gabexate mesilate, the substance accidentally leaked from the infusion site in his elbow. One month later, a dark red erythema and induration accompanied by severe pain appeared in the area proximal to the gabexate mesilate injection site. The biopsy specimen demonstrated no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Case 1 presented with typical clinical features of bullous PG. In Case 2, we at first suspected myeloma cells infiltration in the skin, because previous reports showed that leukemia cells recruited to the sites of leakage of a drip infusion on the forearm [3]. However, histological features denied atypical cells and demonstrated PG.…”
mentioning
confidence: 92%
“…Case 1 presented with typical clinical features of bullous PG. In Case 2, we at first suspected myeloma cells infiltration in the skin, because previous reports showed that leukemia cells recruited to the sites of leakage of a drip infusion on the forearm [3]. However, histological features denied atypical cells and demonstrated PG.…”
mentioning
confidence: 92%